Повышение достоверности расчетов при решении уравнений интегральной модели пожара - Makarov, Евгений; Polevoda, Иван; Demenchuk, Александр; Krasovskiy, Сергей; Osyaev, Владимир (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
The methods for validity improvement of fire integral model based on the constitutive law in differential equations of equilibrium at fire are represented.